2018
DOI: 10.1186/s12887-018-1137-4
|View full text |Cite
|
Sign up to set email alerts
|

Opioid substitution treatment and heroin dependent adolescents: reductions in heroin use and treatment retention over twelve months

Abstract: BackgroundOpioid dependence is a major health concern across the world and does also occur in adolescents. While opioid substitution treatment (OST) has been thoroughly evaluated in adult populations, very few studies have examined its use in adolescents. There are concerns that OST is underutilised in adolescents with heroin dependence. We sought to measure changes in drug use among adolescents receiving OST and also to examine treatment attrition during the first 12 months of this treatment.MethodsWe include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…One study conducted among patients receiving methadone treatment in Israel during 2004–2005 found a positive association between amphetamine use during treatment measured by UDS and retention over 13 months [ 47 ]. Eight studies found no significant association [ 36 , 48 54 ]. Three studies did not report tests of statistical significance [ 55 57 ], with one noting that there were “too few patients to perform statistical comparison” for this association [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study conducted among patients receiving methadone treatment in Israel during 2004–2005 found a positive association between amphetamine use during treatment measured by UDS and retention over 13 months [ 47 ]. Eight studies found no significant association [ 36 , 48 54 ]. Three studies did not report tests of statistical significance [ 55 57 ], with one noting that there were “too few patients to perform statistical comparison” for this association [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies found a significant negative association between amphetamine use disorder or methamphetamine/amphetamine use and opioid abstinence during MOUD treatment [ 58 61 ]. The other 4 studies found no significant association [ 54 , 62 64 ]. There were no clear patterns in findings across studies with respect to study design, time period, geographic location, or definition of predictors/outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, early onset of smoking or alcohol use in adolescence is associated with suicide attempts among females. Thus, among OAT patients, where hard substance use is common during adolescence or early adulthood [ 23 ], several of these medical and psychosocial risk factors for suicide attempts are often presented. This might be a significant reason for the high prevalence of suicide attempts among OAT patients and should lead to close clinical monitoring for suicide risk in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Patients receiving OAT usually have a history of hard injecting opioid use, often initiated in adolescence or early adulthood [ 23 ]. Additionally, polysubstance use, including substances used alongside OAT opioids, is common among OAT patients, with a prevalence of up to 70 % in this population [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, preventing ACEs in a single generation or reducing their impact on children can benefit not only those individuals but also future generations. Research shows that there is a significant reduction in opioid use amongst adolescent patients receiving OAT which further compounds the need to intervene as early as possible in their treatment [ 43 ]. Public Health will play a central role in breaking the cycle of violence but they will require help and support from health care services such as Drug and Alcohol Services [ 39 ].…”
Section: Discussionmentioning
confidence: 99%